Rice parboiling using a dual-powered parboiler: Evaluation of energy consumption patterns and milling quality - Sanusi Mayowa Saheed; Sunmonu Musliu Olushola; Olaleye Sodiq Ayinde; Adedeji Ifeoluwa Benjamin; Adeniyi Harris Olamiposi; Eniola Adebayo (Acta Periodica Technologica, 2022)
Energy plays an important role in rice processing whereby the amount of energy consumed could influence the cost of production. Therefore, this study aimed to evaluate the energy consumption and milling quality of three rice varieties (FARO 15, FARO 60 and FARO 62) using a dual-powered rice parboiler. The energy consumption patterns viz steeping energy consumption, steaming energy consumption, total energy consumption and energy intensity of the rice varieties using electricity and Liquefied Petroleum Gas (LPG) combustion as the power source of the parboiler were determined using standard equations. The milling quality in terms of milling recovery and head milled rice were also determined using standard procedures. The energy consumption during steeping and steaming ranged from 39.02 MJ to 40.00 MJ and 12.90 MJ to 14.09 MJ, respectively. The total energy consumption and energy intensity ranged from 31.62 MJ to 32.01 MJ and 7.90 MJ/kg to 8.00 MJ/kg, respectively. The milling recovery and the head milled rice of the rice varieties ranged from 64.23% to 66.76%, and 55.45% to 59.18%, respectively. The total energy consumption and energy intensity of the rice varieties differ based on the power source of the rice parboiler. The power source also influenced the milling recovery and head milled rice of the rice varieties. The use of gas as a power source for the rice parboiler consumed more energy than electricity. The information provided in this study would guide energy conservation, prevention of production downtime and improving rice milling quality.